Aktivitas Dakwah Melalui Metode Cawisan di Majelis Inaayatul Qubro Desa Teluk Kecapi Kecamatan Pemulutan Kabupaten Ogan Ilir - Rizkydermawan; Choiriyah; Muslimin (Pubmedia Social Sciences and Humanities, 2024)
Da'wah is an important aspect of the Islamic religion which aims to spread religious teachings to the wider community. One of the da'wah methods that has been used at the Inaayatul Qubro Council is the Cawisan method. Cawisan is a place to prepare to listen to religious recitations or lectures delivered by Ulama or Ustadz (teachers) providing explanations of religious issues while the congregation listens and continues with questions and answers. This research aims to find out how da'wah activities use the cawisan method in the Inaayatul Qubro assembly, Teluk Kecapi Village, Pemulutan District, Ogan Ilir Regency and the Supporting and Inhibiting Factors. The research uses descriptive qualitative methods with data collection techniques of observation, interviews and documentation. In this research, behaviorist communication theory is used. The results of this research show that after attending the cawisan the congregation began to understand the benefits of studying Islamic teachings not only understanding them but being able to practice positive activities in daily life to achieve happiness in this world and the hereafter and show changes towards the better in accordance with Habib's teachings. as well as changes in behavior and thought patterns, this is proven by the increasing number of Cawisan members, and they are willing to attend every meeting. Cawisan method, namely Islamic teaching delivered in the mosque. The congregation in the mosque forms a circle facing the habib who is delivering material in the mosque. Habib and his congregation sat on the floor on the mosque shelf with their legs crossed. The material presented has been arranged systematically and continuously from one material to the next. The implementation of Cawisan is an activity that is held periodically, namely once a month, with learning using books. This event is usually held in the evening, especially after Isha prayer time, at the Al Wustho Mosque which is located in Teluk Kecapi Village, Pemulutan District, Ogan Ilir Regency. This activity went through several series of activities, namely: Opening, Reading of Maulid Ad-Dhiyaul Lami, Mahalul Qiyam, Closing Prayer, Reading of Maulid, Lecture on the Muqoddimah Al-Hadhromiyah Book, Question and Answer Session, Prayer, Eating Together, Closing.